2020
DOI: 10.3847/1538-4357/abbd40
|View full text |Cite
|
Sign up to set email alerts
|

Precision Orbital Dynamics from Interstellar Scintillation Arcs for PSR J0437–4715

Abstract: Intensity scintillations of radio pulsars are known to originate from interference between waves scattered by the electron density irregularities of interstellar plasma, often leading to parabolic arcs in the two-dimensional power spectrum of the recorded dynamic spectrum. The degree of arc curvature depends on the distance to the scattering plasma and its transverse velocity with respect to the line of sight. We report the observation of annual and orbital variations in the curvature of scintillation arcs ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 45 publications
6
75
0
Order By: Relevance
“…The high-quality secondary spectra from our observations allow for precise curvature measurements for the scintillation arcs. Our analysis of the secondary spectra arc curvatures made use of the scintools 4 Python module (described in Reardon 2018Reardon , 2020. This tool set has recently been used in measuring the orbital parameters of PSR J0437−4715 via the variations in arc curvatures modulated by the pulsar orbit and the Earth orbit (Reardon et al 2020), providing an independent analysis to those of pulsar timing measurements (Perera et al 2019).…”
Section: Arc Curvature Measurementmentioning
confidence: 99%
See 4 more Smart Citations
“…The high-quality secondary spectra from our observations allow for precise curvature measurements for the scintillation arcs. Our analysis of the secondary spectra arc curvatures made use of the scintools 4 Python module (described in Reardon 2018Reardon , 2020. This tool set has recently been used in measuring the orbital parameters of PSR J0437−4715 via the variations in arc curvatures modulated by the pulsar orbit and the Earth orbit (Reardon et al 2020), providing an independent analysis to those of pulsar timing measurements (Perera et al 2019).…”
Section: Arc Curvature Measurementmentioning
confidence: 99%
“…Our analysis of the secondary spectra arc curvatures made use of the scintools 4 Python module (described in Reardon 2018Reardon , 2020. This tool set has recently been used in measuring the orbital parameters of PSR J0437−4715 via the variations in arc curvatures modulated by the pulsar orbit and the Earth orbit (Reardon et al 2020), providing an independent analysis to those of pulsar timing measurements (Perera et al 2019). It has recently been suggested that particular scattering screen morphologies will cause the apex of the parabolas in the secondary spectrum to be offset from the origin (Shi 2021).…”
Section: Arc Curvature Measurementmentioning
confidence: 99%
See 3 more Smart Citations